Relato de um certo Eldorado : estudo do romance Órfãos do Eldorado, de Milton Hatoum - Morais, Elival de Souza (2019)
Study about the aspects cultural-historically from the myth, of the social and familiar relations, as well as narratives and voices present in the literary production of the Amazonian writer Milton Hatoum, specifically circumscribing, the novel Orphans of Eldorado (2008). In this form, it gives itself the reading of a contemporary writer who has been taking root in his work myth, memory, history and society. The study prosecutes from the themes: traditional myth, his definitions and importance; native erotic narratives; social and familiar conflicts, as well as decadence, subjects that make possible to understand the work inside the Amazonian space. Like consequence of these conflicts, it talks as to the development project for the Amazon region and the end of the Second Cycle of the Rubber reaching the current days with the introduction of the Zona Franca of Manaus, causing a special glance for Amazon region.